KITAB SULLAM AN-NAYYIRAIN DALAM TINJAUAN ASTRONOMI MODERN - Muhammad Teguh Shobri (An Nisa'a, 2014)
For Indonesian Moslem, the determination of the month of Ramadlan, Shawal and Zulhijjah is based on two methods namely, rukyat and hisab. At the same time, the beginning of these three months is determined according to the results of rukyat. Besides that, they are also determined by hisab method. The determination of other months is based on hisab. The development of the two methods seem imbalanced, at the beginning, rukyat was only meant as an effort to see hilal at the beginning of a new month, the 29th Qomariah month. This method did not use a sophisticated equipment to be used to see small thing bigger and used as the only method to determine the beginning of the month of Ramadlan, shawal and Zulhijjah.ملخص: شهرالرمضان، شوال, وذوالحجة – المسكان اندونسيين قد قرر بطريقتين. أولا طريقة الرؤية ثانيا طريقة الحساب. في بعض الاحيان قرر هذا الشهر الثلاثة بالرؤية وحين أخر قرر بالحساب. أما قرر أول الشهر فى الأشهر الباقى يكفى بالحساب. تطور هذان طريقتان لايقسا وتيان. فى الاول، انما الرؤية تقصد بها كمحاولة رؤية الحلال فى أول شهر جديد فى التاريح 29 شهر قمرية بعين كاشفة، بالعبارة الاخرى الرؤية تكون نعيرالة وتعتبرا الطريقة الوحدة فى القرار أول شهر الرمضان، شوال وذوالحجة، ثم عملية الرؤية تطور بائباحة اسة خدام الالة للنظر شيئا بعيدا أكبر وأظهر مثلا باستخدام المظهر حينما يتطور الفهم على نصوص الدين وبعد العلماء يفتحون انفسهم لاعتماد على الحساب- وليست الرؤية فقط – فى تقرير اول الشهر القمرية، الرؤية ليست هى الطريقة الوحيدة فى تقرير اول شهر جديد، يوجود ذلك التغير يجعل الحساب اشد تطورا حتى يبعث تنوع منهاج الحساب كما حدث فى اندونسيا.